A Miniature L-slot Microstrip Printed Antenna for RFID - Mohamed Ihamji; El hassane Abdelmounim; Jamal Zbitou; Hamid Bennis; Mohamed Latrach (Universitas Ahmad Dahlan, 2018)
This work presents a miniature microstrip antenna at 2.45 GHz by using the slots technique. This microstrip antenna is fed by a CPW technique and designed for RFID reader system on FR4 substrate. A size reduction equal to 66.6% has been obtained compared to the conventional rectangular microstrip antenna. The total area of the final circuit is 19x31 mm2. The validated antenna has good matching input impedance with a stable radiation pattern, a loss return of -40 dB, and a gain of 1.78 dBi, a prototype of the proposed antenna has been fabricated and measured.